Upstream-downstream asymmetries of drought impacts in major river basins of the European Alps - Dahlmann, Heindriken; Stephan, Ruth; Stahl, Kerstin (Frontiers in Water, 2022)
The European Alps, despite being Europe’s water towers, are increasingly affected by droughts. In recent decades, when climate warming has intensified, drought impacts have illustrated the regions’ vulnerability. Improved knowledge on the spatial distribution of drought impacts from high elevation headwater regions down to plateau and foothill areas is of tremendous importance to understand socio-economic drought dimensions. The region has an exceptional data availability including archived drought impact information. It is therefore a good test bed for the often-assumed general hypothesis that drought impacts become more severe downstream. The aim of this study was to investigate whether upstream-downstream differences in the distribution of drought impacts exist in the four major river basins of the European Alps - Rhine, Rhone, Po and Danube. Two different classifications were developed to divide these basins in up- and downstream areas. We based the first classification on the distances to the main sink, and the second classification on human influence. The EDIIALPS database provided qualitative data to analyze the distribution patterns of reported drought impacts from 2000-2020. The results suggest a strong regional variability regarding the temporal and spatial distribution of drought impacts within the individual basins. But they support the general hypothesis: for both classifications the number of drought impacts per area is higher in downstream regions. For the classification based on distances differences are statistically significant for the Rhine and Danube basin. Further, the analysis of the drought indices SPI-6 and SPEI-6 revealed that the drought event does not have a large impact on the upstream-downstream differences. The study provides insight into the spatial distribution of drought impacts in the four major river basins of the European Alps and support for the existence of upstream-downstream asymmetries. Climate change and enhanced cascading effects likely increase these asymmetries and consequently future drought management strategies should take them into account.